Uji Aktivitas Ekstrak Etanol Daun Bandotan (Ageratum conyzoides L) Terhadap Penyembuhan Luka Bakar Pada Tikus (Rattus norvegicus) Dengan Diabetes Melitus - Afika, Nur; Yunus , Muhammad; Novriani , Erida (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Burn wounds in patients with diabetes mellitus experience impaired healing due to chronic hyperglycemia. This study aims to identify phytochemical compounds, analyze the characteristics of crude drugs, and test the activity of ethanol extracts of bandotan leaves (Ageratum conyzoides L.) on burn wound healing in rats (Rattus norvegicus) with diabetes mellitus, including histological evaluation of wound tissue. Screening results showed that the extract contains active compounds such as alkaloids, flavonoids, tannins, saponins, quinones, and steroids. Herbal material characterization met standards for moisture and ash content but did not meet standards for water-soluble and ethanol-soluble extract content. The extract gel formulation was tested at three concentrations (5%, 10%, 15%). Efficacy tests showed that the 15% gel accelerated wound healing by 100% by day 15, with histological findings indicating increased numbers of fibroblasts, collagen fibers, and capillary blood vessels. This study concludes that ethanol extract of bandotan leaves has potential as an effective wound healing agent, particularly in diabetic conditions.